Endothelial cell dysfunction: Implications for the pathogenesis of peripheral artery disease - Kavurma, Mary M.; Bursill, Christina; Stanley, Christopher P.; Passam, Freda; Cartland, Siân P.; Patel, Sanjay; Loa, Jacky; Figtree, Gemma A.; Golledge, Jonathan; Aitken, Sarah; Robinson, David A. (Frontiers in Cardiovascular Medicine, 2022)
Peripheral artery disease (PAD) is caused by occluded or narrowed arteries that reduce blood flow to the lower limbs. The treatment focuses on lifestyle changes, management of modifiable risk factors and vascular surgery. In this review we focus on how Endothelial Cell (EC) dysfunction contributes to PAD pathophysiology and describe the largely untapped potential of correcting endothelial dysfunction. Moreover, we describe current treatments and clinical trials which improve EC dysfunction and offer insights into where future research efforts could be made. Endothelial dysfunction could represent a target for PAD therapy.